2018
DOI: 10.3390/nu10050587
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Processed Food Consumption and Chronic Non-Communicable Diseases-Related Dietary Nutrient Profile in the UK (2008–2014)

Abstract: We described the contribution of ultra-processed foods in the U.K. diet and its association with the overall dietary content of nutrients known to affect the risk of chronic non-communicable diseases (NCDs). Cross-sectional data from the U.K. National Diet and Nutrition Survey (2008–2014) were analysed. Food items collected using a four-day food diary were classified according to the NOVA system. The average energy intake was 1764 kcal/day, with 30.1% of calories coming from unprocessed or minimally processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
359
8
40

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 446 publications
(464 citation statements)
references
References 33 publications
(58 reference statements)
27
359
8
40
Order By: Relevance
“…High consumption of ultraprocessed foods is associated with nutritionally unbalanced diets. High energy density and higher total fat, saturated fat, and free sugars, along with lower protein and fibre content are common constituents of dietary patters based on ultraprocessed foods (da Costa Louzada et al, b ; Moubarac et al, ; Steele et al, ; Rauber et al, ). In addition, increasing evidence suggests that these foods are harmful to health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High consumption of ultraprocessed foods is associated with nutritionally unbalanced diets. High energy density and higher total fat, saturated fat, and free sugars, along with lower protein and fibre content are common constituents of dietary patters based on ultraprocessed foods (da Costa Louzada et al, b ; Moubarac et al, ; Steele et al, ; Rauber et al, ). In addition, increasing evidence suggests that these foods are harmful to health.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main shifts in dietary patterns across the globe is the increase in consumption of ultraprocessed foods (Pan American Health Organization, ; Stuckler, McKee, Ebrahim, & Basu, ). These foods are problematic not only because they are associated with higher dietary content of energy, fat, sugar, and sodium (Steele, Popkin, Swinburn, & Monteiro, ; Moubarac, Batal, Louzada, Steele, & Monteiro, ; Rauber et al, ; da Costa Louzada et al, b ) but also because they are developed to be palatable, convenient, and cheap in order to encourage purchase and subsequent excessive consumption (Monteiro, Levy, Claro, de Castro, & Cannon, a ; Ludwig, ; Moodie et al, ). Studies conducted in high and middle‐income countries showed positive associations between consumption of ultraprocessed foods and both weight gain and chronic diseases in several age groups (Tavares, Fonseca, Rosa, & Yokoo, ; Rauber, Campagnolo, Hoffman, & Vitolo, ; da Costa Louzada et al, a ; Monteiro et al, d ).…”
Section: Introductionmentioning
confidence: 99%
“…Ultra‐processed foods are typically energy dense products, high in sugar, unhealthy fats, and salt, and low in dietary fiber, protein, vitamins, and minerals . As a result, dietary patterns based on these food products are associated with diets of lower nutritional quality, especially with regards to the added sugars content …”
Section: Introductionmentioning
confidence: 99%
“…4 Compared with the rest of the diet, ultraprocessed foods often have a higher content of total fat, saturated fat, added sugars, and salt, along with a low amount of fiber and low vitamin density. [5][6][7] In addition, they can contain neo-formed contaminants derived from physical, chemical, and biologic processes, along with substances from packaging and additives. 8,9 Moreover, epidemiologic evidence has demonstrated that ultra-processed food consumption is associated with poorer diet quality.…”
mentioning
confidence: 99%